2011
DOI: 10.1007/s13197-011-0294-3
|View full text |Cite
|
Sign up to set email alerts
|

Functional properties of pasta enriched with variable cereal brans

Abstract: To explore the potentiality of cereal brans for preparation of fiber enriched pasta, various cereal brans (Wheat, Rice, Barley and Oat) were added at 0, 5, 10, 15, 20 and 25 per cent to durum wheat semolina. The effect of cereal bran enrichment on the colour, cooking, sensory quality and shelf life of enriched pasta was assessed at ambient temperature. Pasta prepared with added fiber at 25 per cent level had the highest protein and dietary fiber content as compared to control. Enrichment with variable fiber so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
136
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(161 citation statements)
references
References 8 publications
23
136
1
1
Order By: Relevance
“…Table 2 revealed that barley flour had positive effect (p≤0.05) on lightness of pasta samples at linear level. Kaur et al (2011) also found increased brightness of wheat pasta incorporated with barley and oat bran. Figure 1(a) represented changes in lightness of pasta as function of barley flour and WPC.…”
Section: Effect Of Variables On Colourmentioning
confidence: 82%
“…Table 2 revealed that barley flour had positive effect (p≤0.05) on lightness of pasta samples at linear level. Kaur et al (2011) also found increased brightness of wheat pasta incorporated with barley and oat bran. Figure 1(a) represented changes in lightness of pasta as function of barley flour and WPC.…”
Section: Effect Of Variables On Colourmentioning
confidence: 82%
“…21 Semolina and jaggery are organic by-products of plants with high nutritive value. [15][16][17][18]22 This might partly explain the positive benefits of the SJ diet on flies.…”
Section: Resultsmentioning
confidence: 99%
“…27,28 Semolina and jaggery are good sources of carbohydrates and proteins. [15][16][17][18]22 Thus, flies reared on the SJ diet were assessed for any changes in body weight and lipid percentage and compared to flies reared on the CSY diet. There was no significant increase in body weight in male and female flies when reared on 10% SJ diet (Fig.…”
Section: Semolina-jaggery Diet Improved Fly Output At F 2 and F 3 Genmentioning
confidence: 99%
See 1 more Smart Citation
“…Prabhakar and Venkatesh (1986) reported similar results working with acid treated brans. According to Kaur et al (2011) free fatty acids (%) for enriched pasta increased with storage period, but the values remained in the acceptable range because of which, the taste, flavour and acceptability of pasta was not much affected. Rice bran enriched pasta supplemented at 15 per cent level had maximum values of free fatty acids (%).This may be contributed to the fact that rice bran contained maximum amount of fat per centage than other cereal brans.…”
Section: Moisture Contentmentioning
confidence: 95%